Sewage monitoring system based on artificial intelligence - Xuan, Lefei; Tu, Xiaojing; Niu, Mengning; Khan Chowdhury, Ahmed Jalal (Technoscience Publications, 2019)
In order to avoid the problems of unstable water quality and high treatment cost caused by manual control of operators in wastewater treatment process, it is proposed to design and develop an intelligent wastewater monitoring system. According to the characteristics of numerous sewage treatment devices and unstable control indexes, the soft sensing technology of dissolved oxygen (DO) concentration is combined with computer automatic control technology to design intelligent monitoring scheme of sewage treatment process. The overall structure and function of the system are given, the control software, DO concentration soft measurement module and operation guidance are introduced, which lays a foundation for the concrete implementation of the system. The results show that the intelligent monitoring scheme and the aeration control method based on DO concentration soft measurement are applied to the sewage treatment field, and the hardware integration design and software configuration development are completed. The man-machine interface designed is intuitive and friendly, and the operation is convenient. After field installation and debugging, it is successfully operated in a sewage treatment plant, making the removal rate of effluent impurities reach the expected goal and achieve obvious economic benefits. Therefore, it is of great scientific significance and application value to strengthen the research and application of intelligent control of sewage treatment system in China.